The Effect of Maltose-Sucrose Weight Ratio in Lozenges of Bajakah Root Ethanolic Extract (Spatholobus littoralis Hassk.) on Their Flavonoid Total Release, Physical, and Sensory Properties - Sholichah Rohmani; Anif Nur Artanti; Dian Eka Ermawati; Chaterine Turu' Padang (UNIVERSITAS SEBELAS MARET (UNS), 2025)
Bajakah root ethanol extracts contain flavonoids, phenolics, and tannins as antioxidants that can inhibit tumor growth. However, consuming the pure extract as a supplement has an unpleasant odor and taste. Providing the extract as lozenges may give better taste, control the release of active substances, be absorbed in the oral mucosa, and avoid first-pass metabolism. Sucrose and corn syrup are the main components of lozenge fillers. This study evaluates the combination of maltose-sucrose on physicochemical properties, drug release, and taste acceptance. Bajakah roots were macerated in 50% ethanol (1:5 w/v) for three days, and the filtrate was evaporated. The extract contained 2.18% and 9.03% of flavonoids and tannins, respectively. The high proportion of sucrose increased hardness, sweet taste, pungent aroma, and better release of active substances, but did not affect the disintegration time. The maltose-sucrose weight ratio of 1:1 was selected because it met the requirements for lozenges based on the Indonesian Pharmacopoeia Edition VI, having characteristics of a weight of 250 ± 9.93 mg; hardness of 9.30 ± 2.08 kg; dissolution time of 10.48 ± 4.26 minutes; and released 80% of active substances for 60 minutes. In addition, this formula is stable in storage and is most preferred by respondents.